Application of modified genetic algorithms for solving evolutionary problems of the theory of schedules - D. S. Zakharov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The article proposes ways to modify genetic algorithms used to automate the process of scheduling.Method. The methods of evolutionary calculations, the theory of schedules, genetic algorithms, the developed software product are used in the work.Result. It is established that the construction of the initial GA population for solving the problem is an extremely important criterion for the convergence of the result. It has been established that the two-stage mutation also allows individuals to be adjusted in the right direction, thereby reducing the time required to perform GA work.Conclusion. Studies show that the developed methods of GA modification can greatly affect the performance of software in the automated scheduling of educational institutions, a scheme of GA operation has been developed, methods of GA modification have been presented and tested.